Manajemen Islam Perusahaan : Model Dan Praktis - Haanurat, Ifayani; Suarni, Agusdiwana; Haliding, Safri (Jurnal Ekonomi Balance, 2012)
Islamic syariah is a comprehensive guide of life,  covering  of all aspect of life. Syariah is not only set the rule  of the transcendental relationship between muslim and Allah  SWT but provided for every aspect, one of the rules is organizing institutions. Therefore, Islam has also Islamic management concept  Islamic management reguires the leaders of organization are able to do a holistic approach with the God concept by giving their outhority to the God with humility, responsibility and independence to fulfill their duties and practice Islamic management with flexible  model  for maximum result.Islamic management of organization should be viewed as a means to facilitate the implementation of Islamic in the activities of the organization. Implementation of Islamic values as intangibles in our thinking and activities in all aspects of organization. Thus, The values of Islamic is actually the organization’s core values. The  Islamic values will become the strategic of organization.